Analisis Saluran Pemasaran Lima Pangan Pokok dan Penting di Lima Kabupaten Sumatera Utara [Analysis of Marketing Channel of the Five Essentials and Important Food in Five Districts of North Sumatra] - Muhammad Ilham Riyadh (Pusat Penelitian, Badan Keahlian DPR RI, 2018)
The lack of equal distribution of food, and the imbalance of distribution channels from producers to consumers shows that the production systems and distribution systems of some foods are disrupted because the quality of transportation facilities and infrastructure is much damaged so that price increases at the consumer level are far greater than the price increases at the producer level. The research objectives are to analyze (1) the supply channel of food commodities, (2) the efficiency of trading in each trading channel, and (3) the trade policy of food commodities. This research was conducted in North Sumatra Province with 5 Districts having superiority in food commodities, namely Simalungun (rice), Karo (corn), Dairi (red onion), North Tapanuli (red chili), and Langkat (beef). Methods of analysis of trading margins, farmer’s share, and B/C ratio. The length of the marketing channel will increase the price disparity so that it can harm farmers and consumers. Rice commodities experience 132 percent high disparity and the highest profit ratio of farmers for red chili commodities is 45.31 percent. The highest farmer share of red chili is 89 percent. The structure of the market structure faced by farmers of rice, corn, shallots, red chili, and beef cattle tends to be imperfect market competition. The price of the agreement between the seller and the buyer is the result of the bargaining, while the way the buyer payments for the price of the agreement can be in cash and installments. One of the effort that can be done to improve marketing efficiency is to prepare a strong and skilled farmer institution in entrepreneurship in an effort to foster farmers and specialize in the delivery and marketing of commodities.Keywords: trading, food, marketing channels, farmer share, revenueAbstrakKurang meratanya ketersediaan pangan dan timpangnya jalur distribusi dari produsen ke konsumen akibat kualitas sarana dan prasana transportasi yang rendah akan menstimulasi kenaikan harga di tingkat konsumen jauh lebih besar dibandingkan dengan kenaikan harga di tingkat produsen. Tujuan penelitian ini adalah untuk menganalisis (1) saluran pemasaran komoditas pangan, (2) efisiensi tata niaga pada setiap saluran pemasaran, dan (3) kebijakan tata niaga komoditas pangan. Penelitian ini dilakukan di Provinsi Sumatera Utara dengan 5 daerah kabupaten yang memiliki keunggulan komoditas pangan, yaitu Simalungun (beras), Karo (jagung), Dairi (bawang merah), Tapanuli Utara (cabai merah), dan Langkat (sapi). Metode analisis menggunakan margin tata niaga, farmer’s share, dan B/C ratio. Panjangnya saluran pemasaran akan meningkatkan disparitas harga yang tinggi sehingga dapat merugikan petani dan konsumen. Hasil penelitian menunjukkan bahwa komoditas padi mengalami disparitas paling tinggi, yaitu sebesar 132 persen, sedangkan rasio keuntungan petani komoditas cabai merah tertinggi, yaitu sebesar 45,31 persen dan untuk Farmer share tertinggi dicapai komoditas cabai merah, yaitu sebesar 89 persen. Tata struktur pasar yang dihadapi oleh petani beras, jagung, bawang merah, cabai merah, dan daging sapi potong cenderung persaingan pasar tidak sempurna. Harga kesepakatan penjual dan pembeli merupakan hasil dari tawar-menawar, sedangkan cara pembayaran pembeli atas harga kesepakatan bisa dengan cara tunai dan angsuran. Salah satu upaya yang dapat dilakukan untuk meningkatkan efisiensi pemasaran adalah mepersiapkan kelembagaan petani yang kuat dan terampil dalam kewirausahaan guna membina petani serta mengkhususkan diri untuk pelayanan dan pemasaran komoditas.Kata kunci: tata niaga, pangan, saluran pemasaran, farmer share, pendapatan